In patients undergoing valve-sparing aortic root replacement, is reimplantation superior to remodelling?. (13th December 2020) - Maskell, Perry; Brimfield, Matthew; Ahmed, Amna; Harky, Amer
Summary: A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was: in patients undergoing valve-sparing aortic root replacement, is reimplantation superior to remodelling? The purpose of this best evidence topic was to re-review the updated evidence that has become available in the near decade since the previous review published in 2011. Altogether more than 300 papers were found using the reported search, of which 8 papers represented the best evidence to answer the clinical question. The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes and results of these papers are tabulated. The included studies have significant limitations relating to low-level evidence study design, variable outcome collection and limited significance testing with direct comparison. Long-term outcomes such as survival, recurrence of aortic regurgitation and valve reintervention were largely equal between the two procedures across the studies. This review, updated from the previous best evidence topic, continues to suggest that there are no clear recommendations or even consensus to guide clinical decision-making when choosing between remodelling or reimplantation approaches to valve-sparing aortic root replacement. To date, no study provides strong clinical benefit to favour either procedure in terms of perioperative outcomes, medium–long term survival or reintervention of the aortic valve. As such, procedure selection should be based upon patient factors and valve evaluation, combined with surgeon preference and experience. Abstract : A best evidence topic (BET) was constructed according to a structured protocol.